1998
DOI: 10.1172/jci4992
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived interferon gamma is required for inhibition of acute graft-versus-host disease by interleukin 12.

Abstract: We have demonstrated that a single injection of interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
145
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 50 publications
10
145
0
Order By: Relevance
“…Recently, Buhlmann et al (22) demonstrated that donor CD4 ϩ T cells that produce IL-2 and express CD40 ligand are required not only for the induction, but also for the sustained expansion of donor effector CD8 ϩ T cells in C57BL/6 cell-injected BDF 1 mice with acute GVHD. In addition, donor CD4 ϩ T cells seem to play a pivotal role in causing lethal acute GVHD (23). These findings suggest that the decrease in donor CD4 ϩ T cells in DBA/2 cell-injected BDF 1 mice treated with IL-18 may play a role as a negative feedback mechanism in the sustained expansion of donor CD8 ϩ CTL, resulting in the prevention of conversion to acute GVHD.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Buhlmann et al (22) demonstrated that donor CD4 ϩ T cells that produce IL-2 and express CD40 ligand are required not only for the induction, but also for the sustained expansion of donor effector CD8 ϩ T cells in C57BL/6 cell-injected BDF 1 mice with acute GVHD. In addition, donor CD4 ϩ T cells seem to play a pivotal role in causing lethal acute GVHD (23). These findings suggest that the decrease in donor CD4 ϩ T cells in DBA/2 cell-injected BDF 1 mice treated with IL-18 may play a role as a negative feedback mechanism in the sustained expansion of donor CD8 ϩ CTL, resulting in the prevention of conversion to acute GVHD.…”
Section: Discussionmentioning
confidence: 90%
“…The role of IFN-␥ levels in regulating GVHD has not been entirely resolved; sustained high IFN-␥ production can result in more severe GVHD in some models (19,25). However, the link between high IFN-␥ and worse GVHD is not a universal finding, with some studies showing reduced GVHD associated with increased donor T cell apoptosis (20,26,27). Therefore, any propensity toward an increased division rate that might occur when the PD-1/PD-L pathway is blocked may be offset by an increased apoptosis rate caused by IFN-␥ elevation.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Other data have suggested that Th1 cytokines reduced acute GVHD or that Th2 cytokines worsened acute GVHD. [28][29][30] In any case, it may be important to regulate both Th1 and Th2 cytokines to control GVHD, and thus CD4 þ and CD4 À Va24 þ NKT cells likely play some roles in preventing acute GVHD.…”
Section: Discussionmentioning
confidence: 99%